2015
DOI: 10.1111/hiv.12274
|View full text |Cite
|
Sign up to set email alerts
|

Liver toxicity and risk of discontinuation in HIV/hepatitis C virus‐coinfected patients receiving an etravirine‐containing antiretroviral regimen: influence of liver fibrosis

Abstract: Our data suggest that etravirine is a safe option for HIV/HCV-coinfected patients, including those with significant liver fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
(26 reference statements)
0
9
0
Order By: Relevance
“…However, in spite of this success, there are still adverse effects incurred from HAART (5) including hepatotoxicity (6), nephrotoxicity (7) and neurotoxicity (8), following large-scale clinical trials on humans as well as animal experimental studies. In addition, there are concerns that the treatment-related drop in morbidity and mortality may actually be overestimated (4) as most studies relies on health-related quality of life outcomes considering only mortality and ignoring treatment-related morbidities.…”
Section: Introductionmentioning
confidence: 99%
“…However, in spite of this success, there are still adverse effects incurred from HAART (5) including hepatotoxicity (6), nephrotoxicity (7) and neurotoxicity (8), following large-scale clinical trials on humans as well as animal experimental studies. In addition, there are concerns that the treatment-related drop in morbidity and mortality may actually be overestimated (4) as most studies relies on health-related quality of life outcomes considering only mortality and ignoring treatment-related morbidities.…”
Section: Introductionmentioning
confidence: 99%
“…When compared directly with EFV in phase 3 clinical trials, grade 3 or 4 elevations in ALT or AST were less common with RPV: ALT 4% EFV versus 1% RPV; AST 4% EFV versus 2% RPV [14][15][16]. The rate of hepatic adverse drug reactions was not statistically significantly different between ETR and placebo in the phase 3 clinical trials of ETR in antiretroviral treatment-experienced patients (DUET-1 and DUET-2) [17].…”
Section: Nonnucleoside Reverse Transcriptase Inhibitorsmentioning
confidence: 94%
“…A review of the literature clearly shows that first-generation NNRTIs exert significant hepatotoxicity, unlike their second-generation counterparts, which seem to be safe for the liver, even in patients coinfected with hepatitis viruses. It is of note that there are various reports of a lack of association of the presence of advanced LF or cirrhosis with an increased risk of grade 3 or 4 TE in HIV patients exposed to second-generation NNRTIs [ 39 , 40 ]. The lower incidence and severity of hepatic toxicity reported with second-generation NNRTIs is related to the rare occurrence of hypersensitivity reactions and the lower potential for induction of liver enzymes exerted by these drugs.…”
Section: Mechanisms Of Nnrti-induced Liver Injurymentioning
confidence: 99%
“…It is a suitable replacement for patients who are virally suppressed on other NNRTI but have developed toxicities and has become an alternative in HIV/HCV coinfected patients because of its safety and lack of interactions with anti-HCV drugs [ 103 ]. Several studies have shown the safety of ETR regarding liver function [ 52 , 104 ], including in HIV/HCV-coinfected patients with significant LF [ 40 , 105 ]. Regarding metabolic alterations, an initial study with ARV-experienced patients reported no clinically relevant changes over the 24-week study period after initiation of ETR treatment, with grade 3 or 4 changes in lipid, hepatic, and pancreatic laboratory parameters being similar to those in the placebo group [ 106 ].…”
Section: Mechanisms Of Nnrti-induced Liver Injurymentioning
confidence: 99%